Persistent lymphocytopenia in convalescent patients with COVID-19: dysregulated B cell, CD4+ T cell, and treg compartments in 7–12% of moderate-severe cases - An, Hui; Yu, Tongtong; Wang, Anlan; Hu, Hao; Zhang, Chen; Wang, Yongyu; Li, Ming (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundLong COVID manifests with heterogeneous clinical outcomes, potentially linked to immune dysfunction. However, the recovery of immune-cell subsets during convalescence remains incompletely understood.MethodsIn this longitudinal cohort, 279 unvaccinated patients with confirmed SARS-CoV-2 infection (13 mild, 218 moderate, 48 severe) were enrolled. Peripheral lymphocyte subsets were analyzed by flow cytometry at admission and at 50 days post-symptom onset (DPSO 50).ResultsTotal T-cell counts normalized in 90–98% of patients in the moderate and severe groups by DPSO 50. Nevertheless, a subgroup exhibited persistent B-cell lymphopenia (<90 cells/µL) in 7.3% of moderate cases (median 77.1 cells/µL, IQR 51.9–83.8) and 12.5% of seltvere cases (median 54.5 cells/µL, IQR 28.4–79.3). Patients with B-cell deficiency also showed concurrent reductions in total T cells, CD4+ T cells, and CD4+CD25+CD127low/FOXP3+ regulatory T cells (Tregs). In moderate cases, CD4+ T cell and Treg counts correlated positively (r = 0.72, p < 0.001), independent of B-cell status, whereas this relationship was absent in severe cases, indicating severity-dependent immune dysregulation.ConclusionsApproximately 7–12% of moderate-to-severe COVID-19 survivors displayed persistent lymphopenia affecting B cells, CD4+ T cells, and Tregs at 50 days post-symptom onset. These findings highlight distinct recovery trajectories and provide insights into Long COVID pathogenesis that may inform therapeutic strategies.